Rainfall Triggered Soil Slope Stabilized with Vetiver Plant - Kumar, Saurabh; Bahadur Roy, Lal (International Journal of Psychosocial Rehabilitation, 2024)
Rainfall has been identified as one of the main causes for slope failures in areas where high annual rainfall is experienced. Vetiver Plant root systems play a major role in the mechanical properties of soil by increasing soil strength and stability, and by increasing the porosity. Soil root matrix bond the soil slope with the mechanical structure technique stabilization used to mitigate the slope failure. Investigation shows that the root framework causes a decrease of water penetration rate, reduce the rate of rising groundwater table, and expanding in soil shear quality. The root-reinforced soil is expected to be of higher strength as well as higher permeability, which would help to reduce runoff by providing more infiltration, thus improving the slope stability. Vetiver root hedges interact with the soil to provide more shearing strength. Rainfall simulator has been designed in laboratory for the observation of the slope deformation, factor of safety, infiltration and seepage flow inside the slope. Numerical analysis of the slope stabilization with Vetiver Plant subjected to different rainfall intensity has been observed by MIDAS Engineering Software. During heavy rainfall Vetiver hedges are very effective to increase the slope stability, maintain the matric suction and reduce the chances of slope embankment failure.